2020
DOI: 10.1007/s00259-020-04810-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliable quantification of 18F-GE-180 PET neuroinflammation studies using an individually scaled population-based input function or late tissue-to-blood ratio

Abstract: Purpose Tracer kinetic modeling of tissue time activity curves and the individual input function based on arterial blood sampling and metabolite correction is the gold standard for quantitative characterization of microglia activation by PET with the translocator protein (TSPO) ligand 18 F-GE-180. This study tested simplified methods for quantification of 18 F-GE-180 PET. Methods Dynamic 18 F-GE-180 PET with arterial blood sampling and metabolite correction was performed in five healthy volunteers and 20 liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…3 and Supplementary Figure S2 ) however showed no significant difference in PSAIF between the groups, and so, all subject PSAIFs were included in the generation of the PBIF. This was also in agreement with other studies [ 27 , 51 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…3 and Supplementary Figure S2 ) however showed no significant difference in PSAIF between the groups, and so, all subject PSAIFs were included in the generation of the PBIF. This was also in agreement with other studies [ 27 , 51 ].…”
Section: Discussionsupporting
confidence: 94%
“…Precisely, the AUC between PSAIF and PBIF was minimized by scaling the PBIF with an arterial blood value at 75 min, as also recommended by past similar TSPO studies [ 27 , 51 ]. It has been shown that venous blood samples may practically be used instead for scaling purpose since arterial and venous blood tend to reach equilibrium at about 30–45 min post-injection time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that venous blood samples may practically be used instead for scaling purpose since arterial and venous blood tend to reach equilibrium at about 30-45 minutes post-injection time (17). Although this was not tested in this work, but similar TSPO studies have also found that PBIF can be appropriately scaled using one blood sample (27,48).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the AUC between PSAIF and PBIF was minimized by scaling the PBIF with an arterial blood value at 75minutes, as also recommended by past similar TSPO studies (27,48). Since our goal is to possibly eradicate arterial sampling, a venous sample can potentially be obtained at 75minutes to scale the PBIF for each subject.…”
Section: Discussionmentioning
confidence: 99%